Antenatal Care Practice and Reasons for Spontaneous Vaginal Delivery at Homein Rural Bangladesh : A Synopsis - Jahan, Ummay Taslima; Mahmud, Sayeed; Dutta, Mukesh Kumar; Deb, Ajoy; Dhali, Balayat Hossain; Islam, Md Serajul (IAHS Medical Journal, 2023)
Background: In the last decade Bangladesh has made significant progress in reducing maternal and child mortality. Still, spontaneous vaginal delivery at home and neglected Antenatal Care (ANC) practice is evident among women of reproductive agein the rural communities.Home delivery assisted by skilled attendants has not reached the expectation. Present study was aimed to evaluate the status of antenatal care practice and the underlying causes of preference of for spontaneous vaginal delivery at home among the rural people. Materials and methods: A descriptive cross-sectional study was conducted over a period of one year (January 2019 December 2019) in selected villages of Feni and Chattogram district. 312 respondents, who were married women in reproductive age (15 – 49 years) and had at least one delivery experience, were interviewed face-to-face by using of a pre-tested mixed questionnaire. Collected data were presented and analyzed by SPSS version-23 software. Results: Majority 67.95% of the respondents attended hospital or clinic for ANC while 32.05% of them didn’t perform it. 68.60% respondents preferred spontaneous vaginal delivery at home and only 31.40% of them preferred institutional delivery. The respondents 51(23.83%) didn’t prefer institutional delivery due to financial matter. Conclusion: Adequate coverage of ANC yet remains poor and women’s attending these services had faced significant gaps in the content of ANC in rural Bangladesh. To reduce maternal mortality, access to health facility for pregnant mothers and inclusion of skilled birth attendants, strengthening the health system is necessary to make birth safer for both mothers and newborns. IAHS Medical Journal Vol 5(2), Dec 2022; 62-66